The influence of reading level of students and readability of textbook among Malaysian ESL secondary school students / Nadzrah Sa’adan - Sa’adan, Nadzrah (2014)
Readability of reading materials is important in the ESL reading classroom because readers can benefit from the reading materials only if there is a proper match between the materials and the readers. Past research suggested that materials difficulty is influenced by many factors such as word difficulty, sentence complexity, sentence length, grammatical familiarity, topic of the materials and formatting feature. However, this study focused only on the sentence length of the reading texts. In addition to that, there is evidence to show that reader can be categorized into three levels which are independent, instructional and frustration reading level. This study investigated the readability level of Form Four English textbook used in Malaysian schools and its relationship with students’ reading level. It is hoped that the findings of this research will encourage more to pay more attention to the material to be presented to students so that it becomes suitable for students’ reading level.